2010
DOI: 10.47102/annals-acadmedsg.v39n8p629
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Outcomes and Cost Between Surgical and Transcatheter Device Closure of Atrial Septal Defects in Singapore Children

Abstract: Introduction: With advances in interventional catheterisation, transcatheter device closure of atrial septal defect (ASD) is now a feasible option to open heart surgery, especially in patients with isolated ASD. We aim to compare the outcomes, benefits and costs between device closure versus standard open-heart surgery for ASD in Singapore. Materials and Methods: This is a comparative study between 2 cohorts with isolated secundum ASDs who underwent closure of ASD either by surgery or device, at the Department… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 22 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Transcatheter closure of secundum ASDs is almost ubiquitously available; compared to surgery, it has the same immediate efficacy and safety but lower morbidity [18,19]. Even in infants below 1 year of age, percutaneous closure is feasible [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcatheter closure of secundum ASDs is almost ubiquitously available; compared to surgery, it has the same immediate efficacy and safety but lower morbidity [18,19]. Even in infants below 1 year of age, percutaneous closure is feasible [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that transcatheter closure results in the normalization of cardiac size and function [9][10][11], and short-and intermediate-term studies have shown the ASO to be safe and effective [12][13][14][15]. Furthermore, it has been demonstrated that the transcatheter mortality and morbidity in this procedure are lower than the surgical approach [2,[16][17][18][19]. Nevertheless, due to the widespread use of this device, a great variety of adverse events have been reported, e.g., device embolization, erosion and cardiac perforations, thromboembolic complications, device infection, residual defects, and others, as discussed in the literature [20].…”
Section: Introductionmentioning
confidence: 99%
“…1 This procedure is an attractive alternative to open-heart surgery because of its shorter hospital stay, faster return to daily life, better cosmetic outcomes, and fewer complications. 2 Percutaneous device closure is a form of interventional cardiac catheterisation that is the first-line treatment for most atrial septal defects because of its well-documented efficacy and minimal morbidity. 3 Percutaneous closure of an atrial septal defect is performed via the femoral vein under local anaesthesia in an alert state in adults.…”
mentioning
confidence: 99%